Work Inequalities in Later Life Redefined by Digitalisation - Introduction of the COST Action DIGI-net - Rasticová, Martina; Krekula, Clary (Magyar Gerontológia, 2024)
The COST Action CA21107, titled "Work Inequalities in Later Life Redefined by Digitalization (DIGI-net)," is an interdisciplinary initiative aimed at exploring the impact of digitalization on work inequalities faced by older workers. As digital transformation reshapes labor markets, it creates unique challenges and opportunities for individuals in later stages of their careers. DIGI-net investigates how digitalization influences employment conditions, career development, and work-life balance for older workers, with particular attention to disparities across gender, socioeconomic status, and cultural contexts.